Sixty Years of Community: St. Olaf Catholic Parish in Eau Claire, Wisconsin, 1952-2012 - Walters, Michaela (My University, 2012)
This paper will explore how the parish community of St. Olaf in Eau Claire, Wisconsin, established in 1952, reflects the Roman Catholic Church, specifically at the local, state, and national levels in the United States. It will also discuss the various changes that have occurred in the past 60 years of its history in terms of the various locations of worship for the members, the growth of the community outreach programs, and the effects of the Second Vatican Council. This ecumenical council was a meeting of Catholic bishops from around the whole that brought reform to the Catholic Church and affected the relationship of the Catholic Church to the world. The parish at St. Olaf has grown from having only 125 families in 1952 to over 1,000 families in 2012.
Keywords: St. Olaf Catholic Church (Eau Claire, Wis.); Eau Claire (Wis.)--Church history; Church work--Catholic Church--History